BRAND-MARKETING OF FUTURE CITIES AS A TOOL FOR ENSURING TERRITORIAL COMPETITIVENESS - Artamonova, Halyna; Yurchenko, Oleksandr; Rudenko, Mykola (Current Problems of Sustainable Development, 2026)
The article examines the theoretical foundations of city brand marketing as a component of the modern system of territorial management and ensuring the competitiveness of territories. Scientific approaches to the interpretation of the concepts of “territorial marketing”, “city brand”, and “territorial branding” are generalized, which made it possible to distinguish marketing-managerial, reputational-image, and investment-competitive approaches to understanding the essence of city brand marketing. The author’s definition of the concept of “city brand marketing” is substantiated and considered as a comprehensive system of strategic management and marketing communications aimed at forming a unique identity, positive image, and competitive advantages of a city. The main structural components of city brand marketing are identified, including strategic-managerial, communication-image, investment-economic, tourism-cultural, and digital-information components, and their role in ensuring the socio-economic development of territories is characterized. The article systematizes the functions and principles of city brand marketing formation, which made it possible to comprehensively characterize its practical significance in the process of territorial development, increasing investment and tourism attractiveness, forming a positive international image, and ensuring social cohesion of the community. It is proved that effective brand marketing is an important tool of strategic city development management, contributes to the intensification of investment activities, the development of the tourism sector, the digitalization of the urban environment, and the enhancement of territorial competitiveness. Particular attention is paid to modern challenges in the development of city brand marketing, including the digitalization of territorial marketing, the development of Smart-City technologies, ESG-oriented development, increased interregional competition, and the post-war recovery of Ukrainian territories. It is substantiated that under wartime conditions, city brand marketing is transformed into a comprehensive mechanism for ensuring socio-economic resilience, international positioning, community support, and attracting investment resources for territorial recovery. The practical value of the study lies in the possibility of applying the proposed approaches in the formation of strategies for the development and promotion of city brands under modern socio-economic challenges.
Keywords: city brand marketing; marketing; territorial marketing; territorial branding; cities of the future; territorial development; digitalization; Smart-City